El covid-19 y su impacto financiero en las empresas PYMES del sector comercio en la ciudad de Loja periodo 2019-2022. - Iñiguez Quezada, María José (2024)
The pandemic due to Covid-19 has brought negative impacts on the SME trade sector. The main objective of this research work was Covid-19 and its financial impact on SME companies in the commerce sector in the city of Loja, period 2019-2022. To achieve the proposed objectives, different types of research, methods and techniques applicable to each study were proposed, having a mixed approach that integrated both quantitative and qualitative elements. In the same way, an exploratory and descriptive research was obtained as a basis. The study sample included a total of 380 SMEs from the commerce sector in the city of Loja. And finally, a non-probabilistic convenience sampling was carried out. Where 15 companies were chosen that had complete information and that, in addition, were the most representative in terms of continuity throughout the years 2019, 2020, 2021 and 2022. During the development of this research, an analysis of small and medium-sized companies in the commerce sector classified under codes G45, 46, 47 in the city of Loja was carried out. The main objective was to evaluate the financial impact caused by the Covid-19 pandemic on these SMEs, focusing mainly on the analysis of financial management. To achieve this objective, the financial results of the years before the pandemic were compared with the years after, covering the period from 2019 to 2022. The financial statements were used to examine each financial indicator and evaluate how the pandemic It affected each of them. This research gave results on how Covid-19 affected commercial SMEs in terms of financial strength. Based on the findings, strategies were developed to guarantee the financial stability of these companies in the future.